First Report of Hop stunt viroid Infecting Citrus Trees in Georgia, USA - Stackhouse, Tammy (Plant disease, 2020)
In recent years, citrus production has rapidly increased within the state of Georgia (USA), and there are now citrus plantings within at least 32 counties in residential, production, and nursery settings. Among the pathogens capable of infecting citrus are viroids, the smallest plant pathogens. Viroids are comprised of circular, single-stranded RNA ranging from 246-463 nucleotides in length (Ito et al., 2002). Hop stunt viroid (HSVd) is one of several viroids known to infect citrus. This viroid has been previously reported within Arizona, California, Florida, Texas, and Washington in the United States and in other locations throughout the world (Hadidi, 2017). HSVd is often spread mechanically on contaminated tools or through grafting. With a wide host range that includes the families Moraceae, Rosaceae, and Rutaceae (citrus), this viroid can easily move throughout a nursery and spread to other plants (Hadidi, 2017). Symptoms of HSVd include a discoloration and gumming of phloem tissues, stem pitting, bark splitting, and chlorotic and stunted growth in susceptible citrus varieties including tangerines and their hybrids (Hadidi, 2017). There are not typically symptoms on leaves or fruits; however, lime plants have shown some yellowing on leaves (Hadidi, 2017). In May and June of 2020, leaf samples were collected from 12 different citrus plants in nursery settings in Berrien and Mitchell counties in Georgia. The cultivars sampled from Citrus reticulata 'Dekopon'. The sampled trees looked relatively healthy with little or no signs of damage, but were selected for testing to ensure that they were viroid free. Reverse transcription-polymerase chain reaction (RT-PCR) was initially used to verify infection with HSVd. Genomic RNA was extracted from the leaf tissue of twelve plants using the TRIzol reagent (Thermofisher, Waltham, MA). Following cDNA synthesis, samples were tested for the presence of HSVd using the primer pair HSVd-F (5'-GGCAACTCTTCTCAGAATCCAGC-3') and HSVd-R (5'-CCGGGGCTCCTTTCTCAGGTAAGT-3') which produces a 302 bp amplicon (Sano et al., 1988). The PCR reactions for nine of the tested samples did not result in the production of any bands, however the other three samples, all Citrus reticulata 'Dekopon', produced the expected amplicon for HSVd. The amplified products were sequenced using Sanger sequencing (Retrogen Inc, San Diego, CA, USA) and the identity of the fragment sequences was confirmed using BLAST analysis (https://blast.ncbi.nlm.nih.gov/Blast.cgi). Partial sequences from these amplicons (deposited as accession number MT632007) shared 99% identity to corresponding HSVd sequences in Genbank (accession number MG779542). In addition to RT-PCR and sequencing, the recombinase-polymerase-amplification (RPA) technology based AmplifyRP® Acceler8™ end-point detection assay (Agdia® Inc., Elkhart, IN) was performed on previously confirmed tissue according to the manufacturer's instructions. This assay also confirmed the presence of HSVd viroid in the three samples that had been previously confirmed via RT-PCR. To the best of our knowledge, this is the first report of HSVd infecting Citrus reticulata 'Dekopon' in Georgia. If this viroid were to spread within the growing Georgia citrus industry, it could pose a significant threat to citrus plantings that contain susceptible varieties. Nursery stock infected with this viroid should be destroyed, and Georgia nursery producers and citrus growers should take appropriate precautions to prevent the spread of this viroid disease, including properly sanitizing tools used for citrus grafting and pruning. Further research is needed to determine the distribution of HSVd and its potential to impact commercial citrus production in Georgia